2019
DOI: 10.1111/cea.13490
|View full text |Cite
|
Sign up to set email alerts
|

Activation through toll‐like receptor 2 on group 2 innate lymphoid cells can induce asthmatic characteristics

Abstract: Background Type 2 innate lymphoid cells (ILC2s) are one of the sources of IL‐5 and IL‐13 in allergic airway inflammation. Innate immune receptors such as Toll‐like receptors (TLRs) expressed on epithelial cells could contribute to ILC2 activation through IL‐33 production, but a direct effect of TLRs on ILC2s remains to be elucidated. Objectives We hypothesized that TLRs can directly activate lung ILC2s and participate in the pathogenesis of asthma. Methods After intranasal administration of IL‐33 to wild‐type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In line with these data, our present study demonstrated a significant increase of TLR2 expression in WT mice post OVA challenge, and this increase was accounted from its induced-expression on various cell types. Previous studies also indicate its wide spectral expression (35)(36)(37), and reports from our group and others have indicated that TLR2 on macrophages (38), group 2 innate lymphoid cells (39) and epithelial cells (40) may contribute to allergic airway inflammation. Furthermore, the increased expression of TLR2 was accompanied with lung inflammation exacerbation in WT mice post OVA challenge in this study.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In line with these data, our present study demonstrated a significant increase of TLR2 expression in WT mice post OVA challenge, and this increase was accounted from its induced-expression on various cell types. Previous studies also indicate its wide spectral expression (35)(36)(37), and reports from our group and others have indicated that TLR2 on macrophages (38), group 2 innate lymphoid cells (39) and epithelial cells (40) may contribute to allergic airway inflammation. Furthermore, the increased expression of TLR2 was accompanied with lung inflammation exacerbation in WT mice post OVA challenge in this study.…”
Section: Discussionmentioning
confidence: 56%
“…When OVA, HDM, or Alternaria was given via inhalation or intranasally, each of them can be recognized and sensed by TLRs reportedly, especially TLR2 (40). Similarly, intranasally given IL-33 is reported can induce direct stimulation of TLR2 on ILC2s (39). However, papain, which is homologous of HDM-derived Der p1, activates innate immune responses in a manner distinct from that of PAPMs and can induce production of an alarmin IL-33 (63).…”
Section: Discussionmentioning
confidence: 99%
“…Allergy, Inc. (Tokyo, Japan). The method for HDM-induced allergic asthma was optimized from our previous reports 9,56,57 .…”
Section: Allergic Asthma Induction Hdm Extract Was Kindly Produced Bmentioning
confidence: 99%
“…The method for OVA-Alum-induced allergic asthma was used from our previous report 56 . C57BL/6N mice were sensitized intraperitoneally with 2 μg of ovalbumin from Sigma-Aldrich (OVA; A5503, Saint Louis, MO, USA) in conjunction with aluminum adjuvant in 0.5 mL of phosphate-buffered saline on days 0 and 14.…”
Section: Allergic Asthma Induction Hdm Extract Was Kindly Produced Bmentioning
confidence: 99%
See 1 more Smart Citation